METODE PENEMUAN HUKUM OLEH HAKIM - Bambang Teguh Handoyo (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2017)
In dealing with a problem, judges sometimes have difficulty resolving the matter because sometimes laws are incomplete or not clear, the judge must find and look for legal (rechtsvinding). Methods of legal discovery with the interpretation there are several types: (1) the interpretation subsumtif, (2) the grammatical interpretation, (3) the interpretation of systematic, (4) historical interpretation, (5) the interpretation soisologis or teleological, (6) the interpretation of comparability, (7) futuristic interpretation, (8) a restrictive interpretation, (9) an extensive interpretation. The method of the invention with the construction law there are 3 types, namely: (1) peranalogian argument or analogy, (2) the argument of a